Post-frontier Resource Governance - Larsen, P. author. aut Link
XIV, 185 p.
Keywords: The author presents an anthropological analysis of the regulatory technologies that characterize contemporary resource frontiers. He offers an ethnographic portrayal of indigenous rights, resource extraction and environmental politics in the Peruvian Amazon.